2017
DOI: 10.1088/1742-6596/821/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulations of homogeneous isotropic turbulence in a dense gas

Abstract: Abstract. A study of turbulence in BZT dense gas flows is performed using DNS. It is shown that for a large but realistic intensity, the turbulence in dense gas flows behaves in a highly compressible manner when the average thermodynamic state lies within the inversion region in which the gas fundamental derivative is negative. A close similarity is observed in the evolution of the kinetic energy when the initial turbulent Mach number and the Taylor Reynolds number are matched regardless of the Equation of Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…So far, few DNS of DG flows have been achieved. DNS of decaying homogeneous isotropic turbulence (HIT) performed by Giauque, Corre & Menghetti (2017) shows that the dynamic Smagorinsky sub-grid-scale model is not able to correctly capture the temporal decay of the turbulent kinetic energy. They extended their analysis by performing a forced HIT highlighting significant differences in the sub-grid scale baropycnal work and the resolved pressure dilatation, which is reduced by a factor of 2 in a DG when compared with a perfect gas (PG) (Giauque, Corre & Vadrot 2020).…”
Section: Introductionmentioning
confidence: 99%
“…So far, few DNS of DG flows have been achieved. DNS of decaying homogeneous isotropic turbulence (HIT) performed by Giauque, Corre & Menghetti (2017) shows that the dynamic Smagorinsky sub-grid-scale model is not able to correctly capture the temporal decay of the turbulent kinetic energy. They extended their analysis by performing a forced HIT highlighting significant differences in the sub-grid scale baropycnal work and the resolved pressure dilatation, which is reduced by a factor of 2 in a DG when compared with a perfect gas (PG) (Giauque, Corre & Vadrot 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At the present time, few authors have achieved DNS of DG flows. Giauque, Corre & Menghetti (2017) have performed a DNS of decaying homogeneous isotropic turbulence (HIT) and concluded that the standard Smagorinski subgrid-scale (SGS) model does not capture correctly the temporal evolution of the turbulent kinetic energy (TKE) by comparing the LES prediction with the DNS reference results. The DNS also evidenced localized flow regions with strongly positive values for the velocity divergence that could correspond to expansion shock waves.…”
Section: Introductionmentioning
confidence: 99%